'Influence poetry once more': Allen Tate and Milton's 'Lycidas'. Issue 2 (May 2019) - Potts, George
Abstract : The standard narrative of the Milton Controversy in the early twentieth century has frequently regarded the New Criticism as part of the modernist antipathy towards Milton, which was fostered by articles such as F. R. Leavis's 'Milton's Verse' (1933) and T. S. Eliot's 'A Note on the Verse of John Milton' (1935). This essay challenges such depictions of two prominent New Critics – Allen Tate and John Crowe Ransom – as inveterately hostile to Milton, arguing instead that he occupies a significant place in their poetry and criticism. By also considering these American writers' debts to Milton as a context in which to situate the early work of a British poet deeply influenced by them, Geoffrey Hill, the essay opens up new perspectives on Milton's transatlantic reception in the mid-century and his importance to modernist poetics.